Difficult Knowledge and Alternative Perspectives in Ontario's History Curriculum - Seguin, Kimberley (Université d'Ottawa / University of Ottawa, 2019)
This study used qualitative research methods to analyze the ways in which difficult knowledge is represented in Ontario’s 2013 and revised 2018 history curriculum (Grades 7, 8, 10). Difficult knowledge promotes serious discussions about weighty topics – often entrenched in collective memory – and invites readers to reflect on the different values, beliefs, and perspectives around such topics. In this study, difficult histories refer to contested depictions of past violence and oppression as they appear in historical narratives and curricular frameworks (Epstein and Peck, 2017). Examining the curriculum using the lens of difficult knowledge allowed me to consider how educators might foster reconciliation through engagement with chapters in Canadian history. The content analysis considered the difficult knowledge topics in history curricula and the approaches proposed to encourage perspective-taking. The study used a critical sociocultural approach to explore how Ontario’s official curriculum represents difficult knowledge using multiple perspectives in general, and Indigenous perspectives, specifically. In an effort to gain a better understanding of the curricular resources currently available, this study contributes to knowledge growth by identifying entry points in the curriculum that serve to help teachers introduce difficult knowledge using disciplinary thinking and Indigenous epistemic themes. The main goal with this research is to provide recommendations to guide policy, research, and practice in the integration of Indigenous perspectives and knowledges in ways that are meaningful to learners.
Keywords: history education; perspective-taking; difficult knowledge; Indigenous consciousness; historical consciousness